2013
DOI: 10.1139/cjfas-2012-0457
|View full text |Cite
|
Sign up to set email alerts
|

Resident rainbow trout produce anadromous offspring in a large interior watershed

Abstract: Rainbow trout (Oncorhynchus mykiss) have diverse life histories, including both freshwater-resident and anadromous “steelhead” life-history forms. Here, we demonstrate that female resident rainbow trout produce anadromous offspring that survive and return to spawn as adult steelhead. This study represents the first successful attempt to quantify steelhead production rates from female resident rainbow trout across a large watershed. Otolith microchemistry (87Sr/86Sr) techniques were used to determine the matern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
69
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(71 citation statements)
references
References 49 publications
2
69
0
Order By: Relevance
“…Likewise, freshwater maturation persists in many, if not all, hatchery steelhead trout stocks after decades of selectively breeding only anadromous adults (Christie et al 2011;Sharpe et al 2007;Sloat and Reeves 2014). Otolith microchemistry revealed that anadromous kelts in the Yakima River basin, Washington, had resident mothers 7% and 20% of the time in each of 2 years of study (Courter et al 2013). Similar observations of residents producing anadromous offspring have been documented in other populations (Zimmerman et al 2009;Zimmerman and Reeves 2000), in addition to female steelhead producing resident offspring .…”
Section: Oregon; Sloat and Reeves 2014supporting
confidence: 60%
See 4 more Smart Citations
“…Likewise, freshwater maturation persists in many, if not all, hatchery steelhead trout stocks after decades of selectively breeding only anadromous adults (Christie et al 2011;Sharpe et al 2007;Sloat and Reeves 2014). Otolith microchemistry revealed that anadromous kelts in the Yakima River basin, Washington, had resident mothers 7% and 20% of the time in each of 2 years of study (Courter et al 2013). Similar observations of residents producing anadromous offspring have been documented in other populations (Zimmerman et al 2009;Zimmerman and Reeves 2000), in addition to female steelhead producing resident offspring .…”
Section: Oregon; Sloat and Reeves 2014supporting
confidence: 60%
“…On the other hand, only two studies estimated heritability within the context of anadromy and residency (h 2 = 0.44-0.56 and H 2 = 0.69-0.77, respectively) (Doctor et al 2014;. Although the studies provide evidence of a heritable component to O. mykiss life histories and for traits related to individual condition (e.g., body growth), they also demonstrate that individuals are not necessarily precluded by parentage from expressing alternative life histories (e.g., Christie et al 2011;Courter et al 2013;Zimmerman and Reeves 2000).…”
Section: Genetic Influencesmentioning
confidence: 79%
See 3 more Smart Citations